Penggunaan Media Pembelajaran Power Point untuk Meningkatkan Minat Belajar Siswa di UPTD SDN Banyuajuh 2 - Rizqy Atthoriqoh (Yayasan Arrahman Nahdlatul Wathan, 2024)
The aim of this research is to analyze the use of learning media to increase students' interest in learning. This research was conducted on class I students at UPTD SDN Banyuajuh 2 Kamal. The method used in this research is the use of qualitative descriptive methods and data collection techniques using observation and interviews. The research results show that one of the factors supporting the success of educational activities is the use of educational media. Learning media is very important to support learning in the classroom, so that it is hoped that a good teaching and learning process can be implemented and have a positive impact on learning outcomes. A good learning process can be supported by the use of educational media to support students' interest in learning.